Strength, durability, and environmental properties of concrete utilizing recycled tire particles for pavement applications. (15th November 2015) - Kardos, Adam J.; Durham, Stephan A.
Highlights: This research investigated the replacement of fine aggregate with recycled crumb rubber from waste tires. The compressive strength, modulus of rupture, split-tension strength, modulus of elasticity, rapid chloride ion penetrability, and freeze–thaw durability were evaluated for concrete mixtures containing up to 50% replacement of sand with crumb rubber. In addition, the leaching potential for hazardous contaminants from the recycled tire was investigated. The results indicate that a replacement level up to 30% is acceptable for concrete mixtures used in pavement applications. Abstract: The Rubber Manufacturers Association reported that approximately 230.7 million tires were disposed in the United States in 2011. Over 197.5 million of these disposed tires are recycled as tire derived fuel, lightweight fill, retaining walls, erosion protection as well as many other marketable uses. The primary objective of this study was to examine an alternative use for the 33.2 million remaining waste tires land disposed throughout the United States. This study used recycled tires in the form of crumb rubber as a fine aggregate replacement in concrete mixtures. Sustainable concrete mixtures for pavement applications that incorporated waste-stream materials such as fly ash, crumb rubber, and recycled concrete aggregate were evaluated for their performance. Fresh and hardened concrete properties were measured on mixtures containing 15% cement replacement with fly ash and sand volume replacements with crumb rubber of 10%, 20%, 30%, 40%, and 50%. The effects of the crumb rubber inclusion were determined by comparing mixtures containing the crumb rubber to a control mixture with only sand as the fine aggregate. Recycled concrete aggregate was included as a 50% coarse aggregate replacement by volume in two mixtures containing 20% and 30% crumb rubber content. The mixtures were tested for fresh concrete properties including slump, air content, unit weight and temperature, and hardened concrete properties including compressive strength, split-tensile strength, modulus of rupture, modulus of elasticity, permeability, and freeze–thaw durability. In addition, tests were conducted to determine whether any volatile organics leached from the crumb rubber concrete. As the crumb rubber content increased, the compressive strength, split-tensile, modulus of rupture, and the modulus of elasticity decreased. The crumb rubber concrete's permeability increased within acceptable levels up to a 40% replacement of sand. The results of this study determined that a 30% replacement of sand with crumb rubber (approximately 5.5% of the total mixture volume) was optimum and produced the necessary fresh and hardened properties for concrete pavement.